Successful establishment and five-year sustainability of a neonatal-specific antimicrobial stewardship program in a low middle-income country - Maalouf, Faouzi I.; Saad, Therese; Zakhour, Ramia; Yunis, Khalid (Frontiers in Pharmacology, 2023)
Antibiotic use varies substantially among neonatal intensive care units (NICUs) without any appreciable impact on outcomes. An increased use of antimicrobials has been reported in low-middle income countries. This raises the concern for potential overuse of antibiotics in a fragile patient population, thus increasing the rates of multidrug resistant organisms and affecting the developing microbiome. The presence of a neonatal-specific antimicrobial stewardship program (NS-ASP) can aid with the judicious use of antibiotics in the neonatal population and thus decrease the overuse of such medications. In this quality improvement project, we established and implemented a NS-ASP with the aim of reducing antimicrobial use in the NICU within a year of starting. Several interventions using a multidisciplinary approach included implementing standard algorithms, direct audit and feedback, and automated hard stops. These series of interventions led to a 35% decrease in antimicrobial usage in the first three months and further decrease was seen with a median of 63% decline for a total of 5 years after project implementation. The use of the most commonly prescribed antibiotics, ampicillin and gentamicin, decreased by 63% and 79%, respectively. There was no evidence that this change in practice affected or jeopardized patient outcomes. Additionally, it showed sustainability and resilience despite the many challenges such as COVID-19 pandemic, political and financial unrest, and healthcare sector collapse. This model-based and multidisciplinary low-cost approach can lead to marked improvement affecting neonatal outcomes and can be replicated in other similar centers.